Survey of abandoned industrial sites in the province of Carinthia (Austria) - methodology and results - Fischer, Wolfgang (Acta Geographica Debrecina Landscape & Environment series, 2008)
The paper in hand mainly addresses the issue of abandoned industrial and commercial sites. The results of a survey form the central content and regards the method of investigation of this survey of abandoned sites in the province of Carinthia, including experiences and recommendations. The survey started with a number of more than 10,000 businesses. After the different steps of the survey (research phase, exploration phase, clarification phase and evaluation phase) 444 sites had to be attributed an increased potential for danger. After these steps followed an evaluation which concerned the priority in regard to the securing and/ or remediation of the abandoned sites. On the basis of certain gathered values, future surveys of abandoned industrial and commercial sites can be calculated fairly exactly.